Policy Development for handling COVID-19 from the Perspective of a Policy Narrative Framework - Khotami Khotami; Irwan Gesmi; Moris Adidi Yogia; Pahmi Amri; Dini Tiara Sasmi (Universitas Teuku Umar, 2023)
The spread of the covid-19 outbreak entered Indonesia since 2020. COVID-19 has had an impact on society and government, so that the government, especially the city of Pekanbaru, has carried out various policy strategies to carry out countermeasures in the spread of Covid-19, but the number of spread of covid-19 still has not decreased significantly. This research aims to develop a policy narrative framework that functions in advocating for the media as well as providing influence in the decision/policy making process. This research used qualitative analysis using the Policy Narrative Framework (NPF) approach. This study found that narratives by government actors and the general public in online news media had an influence on the policy of handling Covid-19. The policy narrative framework approach (NPF) contributes to this research such as elements of the storyline of policy development and the role of actors who are directly involved in policy. The implementation of the COVID-19 vaccine program through social media support can be seen from the existence of four indicators, namely Communication, Resources, Disposition, and Bureaucratic Structure and looking at the message sender’s, recipient and quality of message via social media.